Metal-Free and Scalable Sulfoxide Reduction through the Couple (COCl)2/Et3SiH: Synthesis of Albendazole Hydrochloride - Morales-Manrique, Camilo; Gutierrez-Acevedo, Salima; Adarve-Cardona, Laura; Garay-Talero, Alexander; Gamba-Sánchez, Diego (Synthesis, 2025)
Sulfides are valuable organic compounds and important synthetic intermediates. However, the reduction of sulfoxides to sulfides still lacks general applicability due to challenges such as harsh reaction conditions and the reliance on transition metal catalysts. Here, an extension of a previously reported metal-free reduction of sulfoxides is presented, incorporating a greener approach that, in most cases, eliminates the need for chromatographic purification. This method also enabled to scale up the reduction of albendazole to a multigram scale in excellent yield.
Keywords: albendazole; metal-free; reduction; sulfonium salts; sulfoxides